The Performance of Ross 308 and Arbor Acres Broiler Breeder and their Commercial Broiler in Iraq - Khalid Hamid Hassan (Journal of Global Pharma Technology, 2018)
The broiler industry in Iraq depends on importing or producing hatching eggs by using many commercial broiler breeder, such as Hubbard, Lohmann, Ross 308 and Arbor Acres, to supply hatcheries within the broiler industry in Iraq. The aim of this study is evaluating the performance of the female line of Ross 308 and Arbor Acres broiler breeder, and the performance of its broiler progeny. The chicks of the two genetic groups were reared up from hatch to 35 days of age, and the process was replicated for three hatches. The results showed a significant difference in egg weight between Ross 308 and Arbor Acres female lines (77.68 and 69.62 g. respectively) and a significant difference in albumin weight and shell thickness, while there are no significant differences between the genetic groups in body weight, egg production and number of eggs per hen. There is a significant superiority of Ross 308 compared with Arbor Acres in protein and triglyceride concentrations in blood plasma. There are no significant differences between Ross 308 and Arbor Acres broiler in all growth traits.Keywords: Broiler performance, Hatching eggs, Ross 308, Arbor Acres.